2006
DOI: 10.1164/rccm.200601-027oc
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Urokinase and Video-assisted Thoracoscopic Surgery for Treatment of Childhood Empyema

Abstract: There is no difference in clinical outcome between intrapleural urokinase and VATS for the treatment of childhood empyema. Urokinase is a more economic treatment option compared with VATS and should be the primary treatment of choice. This study provides an evidence base to guide the management of childhood empyema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
250
3
25

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 297 publications
(288 citation statements)
references
References 52 publications
(84 reference statements)
10
250
3
25
Order By: Relevance
“…In a clinical study in the United Kingdom of Great Britain and Northern Ireland, we calculated that the cost per admission for a child with empyema was between 7600 and 11 700 United States dollars (US$). 29 A study in the United States yielded similar estimates. 30 Thus, the 35% increase in empyema admissions observed in Australia following the introduction of the PCV7 has brought an additional expenditure of US$ 126 160-194 220 per year to the Australian health-care system.…”
Section: Discussionmentioning
confidence: 74%
“…In a clinical study in the United Kingdom of Great Britain and Northern Ireland, we calculated that the cost per admission for a child with empyema was between 7600 and 11 700 United States dollars (US$). 29 A study in the United States yielded similar estimates. 30 Thus, the 35% increase in empyema admissions observed in Australia following the introduction of the PCV7 has brought an additional expenditure of US$ 126 160-194 220 per year to the Australian health-care system.…”
Section: Discussionmentioning
confidence: 74%
“…Radiological resolution following empyema in children varies widely. 11 Sonnappa et al 4 found that the majority of patients with treated empyema had abnormal CXRs at 6 months. Satish et al 11 found that complete radiological resolution was as variable as 2-16 months.…”
Section: Discussionmentioning
confidence: 99%
“…He underwent pleural drainage with intrapleural urokinase under adequate antibiotic cover as previously reported. 2,4 The pleural fluid was turbid and confirmed as pus on microscopy. Following a decline in pleural drainage, and minimal pleural fluid on USS, the chest drain was removed.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…One metric often used to compare techniques is the overall patient length of stay (LOS). The three published randomized control studies show that this is similar between tube/fibrinolytics and VATS, has a mean of approximately 10 days, and the decreased invasiveness and lower cost of the IR procedure supports its use as a first-line therapy [30,[32][33][34][35]. Complications occur in less than 3% of patients, including pleural bleeding and broncho- Fig.…”
Section: Empyemamentioning
confidence: 99%